PENDIDIKAN ISLAM BERBASIS MODERASI BERAGAMA - Nurul Indana (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to analyse religious moderation-based learning at MA Al Urwatul Wutsqo Jombang. The study focuses on two aspects, namely the forms of implementation of religious moderation-based learning. The research method used is qualitative based on descriptive study. The data collection techniques used were observation, interviews, and documentation. The data were analysed using data reduction, data presentation, and conclusion drawing methods. The results of this study indicate that religious moderation can be applied at MA Al-Urwatul Wutsqo Jombang through several aspects, namely: first, a curriculum that emphasises a comprehensive and contextual understanding of religion; second, a learning process that encourages mutual respect for differences; and third, the creation of a school environment conducive to the practice of religious moderation. The implementation of religious moderation in Islamic education is expected to produce a young generation with a moderate and tolerant understanding of religion, capable of contributing to maintaining harmony in society, the nation, and the state.